2015
DOI: 10.1016/s1473-3099(14)70772-8
|View full text |Cite
|
Sign up to set email alerts
|

A review of the global burden, novel diagnostics, therapeutics, and vaccine targets for cryptosporidium

Abstract: Cryptosporidium spp are well recognised as causes of diarrhoeal disease during waterborne epidemics and in immunocompromised hosts. Studies have also drawn attention to an underestimated global burden and suggest major gaps in optimum diagnosis, treatment, and immunisation. Cryptosporidiosis is increasingly identified as an important cause of morbidity and mortality worldwide. Studies in low-resource settings and high-income countries have confirmed the importance of cryptosporidium as a cause of diarrhoea and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
703
1
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 808 publications
(764 citation statements)
references
References 151 publications
5
703
1
19
Order By: Relevance
“…However, the concentrations after the fifth dose were predicted. studies will examine whether BKI-1517, BKI-1553, and other newly identified BKIs will be effective at a dosage similar to that used for nitazoxanide in humans (ie, every 12 hours for 3 days), which is presently the only Food and Drug Administration-approved drug for cryptosporidiosis in humans, although it is marginally effective [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the concentrations after the fifth dose were predicted. studies will examine whether BKI-1517, BKI-1553, and other newly identified BKIs will be effective at a dosage similar to that used for nitazoxanide in humans (ie, every 12 hours for 3 days), which is presently the only Food and Drug Administration-approved drug for cryptosporidiosis in humans, although it is marginally effective [15].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, nitazoxanide was shown in a randomized trial to reduce the duration of cryptosporidial diarrhea by approximately 2 days in immunocompetent individuals [14]. However, nitazoxanide has limited efficacy in immunocompromised individuals and is associated with an unacceptably high relapse rate [15]. Further, the mechanism of action of nitazoxanide against Cryptosporidium is unknown, and it is speculated that it may act via a nonspecific immunomodulatory effect [7,16].…”
mentioning
confidence: 99%
“…In turn, chronic infection is characterized by the formation of intracellular tissue cysts in brain and muscular tissues that harbor slowly proliferating bradyzoites. Calcium-dependent protein kinases (CDPKs), encoded by apicoplast-associated genes and, thus, only found in apicomplexan parasites and plants, represent excellent drug targets in several apicomplexans such as Plasmodium falciparum (6), Cryptosporidium parvum (7,8) where novel drug targets are of crucial interest (9), N. caninum (10), Eimeria tenella, and Babesia bovis (11). Excellent correlations between cell activity and CDPK1 inhibition were achieved by compounds from a focused bumped kinase inhibitor (BKI) library.…”
mentioning
confidence: 99%
“…La transmisión de los ooquistes ocurre por la vía fecal-oral, a través de fuentes de agua inadecuadamente tratadas, alimentos contaminados (frutas, vegetales) o inclusive de persona a persona; en el caso de la cryptosporidiosis puede existir un componente zoonótico 1,3 . Para el diagnóstico parasitológico de las coccidiosis intestinales se requiere realizar una técnica con tinción, siendo la de Kinyoun una de las más implementadas; también se han desarrollado técnicas más sensibles y específicas como las de tipo inmunológicas (e.g., inmunoaglutinación de partículas de látex, inmunofluorescencia directa, ELISA) y moleculares (e.g., reacción en cadena de la polimerasa: PCR); sin embargo, las mismas poseen elevados costos 1,3,6,7 .…”
Section: Introductionunclassified